Nestle (Malaysia) Berhad Research On Customer Perception Versus Company Business Strategy - Thanil Selrean, Kalai Selvi (2003)
Through the research , the author could increase her understanding on the customers buying habit, purchasing pattern as well as the strength of Nestle Berhad.